A Meaningful Approach to Learning English: Motivating Autonomous Learning Through a Blog. - Correa Romero, Yulieth Stefany; Díaz Vargas, Catalina; Muñoz Sanabria, Jesser Ammar (Corporación Universitaria Minuto de Dios – UNIMINUTO, 2024)
This qualitative action research explored the effectiveness of using innovative strategies to promote autonomous foreign language learning. It was identified that in an English language institute, students showed low motivation in their autonomous learning, despite the availability of different digital resources. To address this problem, a CALLA-based pedagogical approach was implemented, combining task-based independent learning activities such as blogs and interactive resources. Preliminary results show that the implementation of these strategies significantly improved student motivation and favored the development of learning skills. This demonstrates the potential of an educational blog design based on learning strategies and instructional design to enhance the motivation of autonomous learning of English as a foreign language being a personalized and self-regulated learning experiences.

Esta investigación-acción cualitativa exploró la eficacia del uso de estrategias innovadoras para promover el aprendizaje autónomo de lenguas extranjeras. Se identificó que, en un instituto de lengua inglesa, los estudiantes mostraban baja motivación en su estudio independiente, a pesar de la disponibilidad de diferentes recursos digitales. Para abordar este problema, se implementó un enfoque pedagógico basado en CALLA, que combina actividades de aprendizaje independiente basadas en tareas, como blogs y recursos interactivos. Los resultados preliminares muestran que la implementación de estas estrategias mejoró significativamente la motivación de los estudiantes y favoreció el desarrollo de habilidades de aprendizaje. Esto demuestra el potencial de un diseño de blog educativo basado en estrategias de aprendizaje y diseño instruccional para mejorar la motivación del aprendizaje autónomo del inglés como lengua extranjera siendo una experiencia de aprendizaje personalizada y autorregulada.
To determine the incidence of the development of an ADDIE instructional model, articulating the CALLA learning strategies approach through a blog, on the motivation and autonomous learning of English as a foreign language in three courses of intermediate level (B1) students at the Instituto Británico.
Keywords: CALLA; Blog; learning strategies; autonomous learning; EFL; estrategias de aprendizaje; aprendizaje autónomo; Ingles - Enseñanza; Lenguas Germanicas; Aprendizaje